INNOVATION IN HR RECRUITMENT - Alexander L. Ivanov (Статистика и экономика, 2016)
The article is devoted to research of innovations in HR recruitment. The following issues, related to impact of innovations on recruitment development, are discussed: do innovative technologies mean prospects or threats for traditional recruitment? The research is based on the transformations review, which had an impact on all staff selection areas. The article describes up-to-date approaches and leading practices, which allow to draw a conclusion, that recruitment is highly sensitive against scientific and technical progress and has high innovation potential.